Mirror mirror - Singh, Tarsem; Klein, Marc.; Keller, Jason, 1968-; Goldmann, Bernie; Kavanaugh, Ryan.; Ratner, Brett; Roberts, Julia, 1967-; Collins, Lily, 1989-; Hammer, Armie, 1986-; Lane, Nathan, 1956-; Relativity Media; Yuk Films; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2012)
An exiled princess is assisted by seven rebels in order to reinstate her stolen birthright.
Originally released as a motion picture in 2012.
Special features: Looking through the mirror; Prince and the puppies; trailer.
Director of photography, Brendan Galvin ; editors, Nick Moore, Robert Duffy ; music, Alan Menken.
Julia Roberts, Lily Collins, Armie Hammer, Nathan Lane, Mare Winningham, Michael Lerner, Sean Bean.
Rating: PG.
DVD; NTSC, region 1; widescreen (1.85:1) presentation; Dolby Digital 5.1.
Keywords: Snow White (Tale) -- Drama; Queens -- Drama; Dwarfs -- Drama